ANALISIS FERRO SULFAT DARI LIMBAH BESI - Soebiyanto Soebiyanto (Jurnal Farmasi Indonesia, 2009)
Iron Deficieny Anemia (IDA) is one of msjor micronutrient deficiency in Indonesia. IDA is that Indonesian people suffered from 100 million of population. One of the correct ways IDA problems is suplementation with ferrous sulfate. To can use raw material farmacy, it must fulfilquality standart in Indonesia Pharmacope Edition IV.The aims of research is producing, purification and analyses ferrous sulfate from iron waste. Producing of ferrous sulfate is reacting iron waste with acid sulfuric 25% during 2 days. Separated and purification crystal with recrystalyzation then determination with SEM-EDS analysis. The obtain of research shows ferrous sulfate content Fe 54,46%, O 33,55% and S 11,99%. These results show that ferrous sulfate from iron waste fulfil quality standart in Indonesia Pharmacope.